Bahasa Emotif dalam Komunitas “Marah-Marah” di Media Sosial X: (Analisis Bentuk, Makna, dan Fungsi) - Irma Andini; Agung Pramujiono (Bhinneka: Jurnal Bintang Pendidikan dan Bahasa, 2026)
This study aims to describe the forms, meanings, and functions of emotive language within the “angry” community on social media platform X. This study employs a descriptive qualitative approach using observation and note-taking as data collection techniques. The research data consists of 52 posts containing emotive language. Data analysis was conducted through the stages of data reduction, data presentation, and drawing conclusions using a linguistic approach that encompasses lexical, morphological, syntactic, semantic, and pragmatic aspects. The results of the study indicate that the forms of emotive language are dominated by emotional, evaluative, and abusive vocabulary. It is also characterized by the use of non-standard language variations and letter elongation as markers of emotional intensity. In terms of meaning, emotive language possesses both denotative and connotative meanings, with connotative meanings dominating to describe the speaker’s feelings, such as anger, disappointment, and frustration. Emotive language serves expressive, social interaction, and digital interaction purposes. Thus, emotive language within the “angry” community functions not only as a means of emotional expression but also as a medium for social criticism and interaction in the digital space.